A Study on Graduate Theses Focusing on Violin Pedagogy in Turkey - Arica, Eylem (HACETTEPE UNIV, 2017)
In this study, the aim is to perform situation determination related with theses prepared in violin pedagogy field and to examine the findings placed under microscope from various aspects, in context of violin education system and problems. In line with this aim, similarities and differences between units, based on their preferences related with the research, were handled and the integrity of violin education in Turkey was questioned. Besides, the problems detected about violin education in other researches were related with the findings obtained in this research and accordingly were reviewed within the frame of the source or the reflections of the problems. 109 violin related theses were reached between January 2008 and December 2014 in higher education council national thesis archive and 69 among them were evaluated in terms of the determined criteria. Although studies with similar research tendencies under determined categories were found in theses prepared in music teachership, conservatories and fine arts faculties, it was determined that units conduct researches mostly related with their own units. As a result of relation of study findings with problems mentioned in other researches, problems are observed in integral structuring of violin education system of Turkey.
Keywords: Violin pedagogy; violin education; graduate theses; Turkey; Education & Educational Research